PENGARUH TERAPI TERTAWA DENGAN MEDIA VIDEO WAYANG CENK BLONK TERHADAP KECEMASAN PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA JARA MARA PATI KALIASEM KABUPATEN BULELENG: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2018)
Introduction: Laughing therapy with puppet video Cenk Blonk is a therapy that is usually performed on the elderly who experience anxiety. Method: The research design was pra-eksperimental with design one group pre-post test design with sample of 20 respondents selected by using total sampling technique with sample criterion. Data collection was done through a HARS questionnaire. Result of The study used the test Paired t-test with a level Î±=0,05. The results showed the intensity of anxiety felt by the respondents before being given treatment laughter therapy with puppet video media Cenk Blonk being on a lightly numbered level 5 (25,0%), moderate anxienty 13 (65,0%), severe anxiety 2 (10,0%). After being given treatment to have no anxiety amounted 6 (30,0%), mild anxiety 10 (50,0%), moderate anxiety 4 (20,0%). Test results by using test Paired t-test got value p pre and post (0,000) < Î± (0,05), conclusis That is H0 rejected, and Ha be accepted. So it is concluded there is the effect of laughing therapy with puppet video media Cenk Blonk to anxiety in elderly.